Gambierol Potently Increases Evoked Quantal Transmitter Release and Reverses Pre- and Post-Synaptic Blockade at Vertebrate Neuromuscular Junctions. (15th July 2020) - Molgó, Jordi; Schlumberger, Sébastien; Sasaki, Makoto; Fuwa, Haruhiko; Louzao, M. Carmen; Botana, Luis M.; Servent, Denis; Benoit, Evelyne
Abstract: Gambierol is a marine polycyclic ether toxin, first isolated from cultured Gambierdiscus toxicus dinoflagellates collected in French Polynesia. The chemical synthesis of gambierol permitted the analyses of its mode of action which includes the selective inhibition of voltage-gated K + (KV ) channels. In the present study we investigated the action of synthetic gambierol at vertebrate neuromuscular junctions using conventional techniques. Gambierol was studied on neuromuscular junctions in which muscle nicotinic ACh receptors have been blocked with d-tubocurarine (postsynaptic block), or in junctions in which quantal ACh release has been greatly reduced by a low Ca 2 + –high Mg 2+ medium or by botulinum neurotoxin type-A (BoNT/A) (presynaptic block). Results show that nanomolar concentrations of gambierol inhibited the fast K + current and prolonged the duration of the presynaptic action potential in motor nerve terminals, as revealed by presynaptic focal current recordings, increased stimulus-evoked quantal content in junctions blocked by high Mg 2 + –low Ca 2+ medium, and by BoNT/A, reversed the postsynaptic block produced by d-tubocurarine and increased the transient Ca 2+ signals in response to nerve-stimulation (1–10 Hz) in nerve terminals loaded with fluo-3/AM. The results suggest that gambierol, which on equimolar basis is more potent than 3, 4-diaminopyridine, can have potential application in pathologies in which it is necessary to antagonize pre- or post-synaptic neuromuscular block, or both. This article is part of a Special Issue entitled: Honoring Ricardo Miledi - outstanding neuroscientist of XX-XXI centuries. Graphical abstract: Unlabelled Image Highlights: The synthetic polyether toxin gambierol potently enhanced stimulus-evoked quantal transmitter release. The presynaptic fast K + current was inhibited and the synaptic delay prolonged by gambierol. Gambierol reversed the postsynaptic block produced by d-tubocurarine. Gambierol restored from complete paralysis neuromuscular transmission ex vivo in BoNT/A-poisoned mouse muscle. Gambierol increased the transient Ca 2+ signals in nerve terminals stimulated at 1 and 10 Hz.